Minority Influence: An Agenda for Study of Social Change - Prislin, Radmila (Frontiers in Psychology, 2022)
Minority influence was sparked by Moscovici's (1976) observation about the power of active minorities to instigate social change. This idea invigorated research on social influence, which is evident in a subsequent outburst of studies on minority influence up to the 1990s, followed by a decrease and stabilization in the 2000s and 2010s. In spite of a remarkable scientific output, research on minority influence has not addressed its original question about social change. Rather, it has focused dominantly on the cognitive processes and attitudinal change in response to a minority advocacy or minority mere presence, and, to a lesser degree, to the role of minority influence in decision-making and task groups. To orient research toward social change, a research agenda is presented, along with a few illustrative studies. The proposed agenda focuses on time, interactive (minority ↔ majority), and motivated influence as critical explanatory variables to address in the next phase of research on minority influence in the pursuit of social change.